Effect of Temperature on Diffusivity of Monoethanolamine (MEA) on Absorption Process for CO2 Capture - Emyra Ezzaty, Masiren; Noorlisa, Harun; W. H. W., Ibrahim; Fatmawati, Adam (Penerbit Universiti Malaysia Pahang, 2015)
Diffusion coefficient study gains an interest to know the mass transfer properties of molecules especially in study of the absorption process. The main objective of this study is to investigate the effect of temperature on diffusivity of MEA absorption process for CO₂ capture. Three different values of process temperature were chosen for simulation was carried out at 25°C, 40°C. The MD simulation was carried out at NVE (200ps) and NPT (INS) ensemble in Material Studio 7.0 software.